Novel D3 Selective Dopaminergics Incorporating Enyne Units as Nonaromatic Catechol Bioisosteres: Synthesis, Bioactivity, and Mutagenesis Studies - Doerfler, Miriam; Tschammer, Nuska; Hamperl, Katharina; Hübner, Harald; Gmeiner, Peter (Journal of Medicinal Chemistry, 2008)
Enynes of type 4 and 5 as long chain derivatives of the nonaromatic dopamine D 3 receptor agonist 3 (FAUC 73) were prepared by exploiting chemoselective functionalization of the azido-substituted vinyl triflate 9. Radioligand binding studies indicated excellent D 3 affinity and selectivity over related GPCRs for the terminal alkynes 4c (FAUC 460) and 5c. Biphasic displacement curves gave picomolar K i values for the high affinity binding site of D 3. According to mitogenesis experiments and bioluminescence based cAMP assays, the biphenylcarboxamide 4c and its click chemistry derived triazole analogue 5c behaved as strong partial agonists but relative ligand efficacy significantly depended on the type of functional assay. Site directed mutagenesis involving the mutants D 3 D3.32E, and D 3 F6.51W implied that ligand interactions with D3.32 and F6.51 are highly crucial, giving rise to analogous binding modes for dopamine, classical and enyne type agonists. © 2008 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.lphch.noveld